The Influence of School Culture and Self-Development on Digital-Based Learning Among Junior High School Teachers in Sub Rayon 04, Grobogan Regency - Umi Royani; Endang Wuryandini; Muhammad Prayito (Dinasti Publisher, 2025)
This study is motivated by the low level of teachers' digital competence, as many teachers have limited access to practical training related to digitalized learning. As a result, they face challenges in integrating technology into the teaching and learning process. This issue is influenced by two main factors: school culture and self-development. The aim of this research is to determine the influence of school culture and self-development on digital-based learning among junior high school teachers in Sub Rayon 04, Grobogan Regency. The research uses a quantitative approach with a correlational research design. The population consists of all public junior high school teachers in Sub Rayon 04, Grobogan Regency, totaling 190 individuals. A sample of 129 teachers was selected using proportional random sampling. Data collection was conducted through questionnaires. The data were analyzed using descriptive analysis, prerequisite tests, and hypothesis testing, including simple and multiple linear regression analyses, with SPSS for Windows Release 28. The results show that school culture has a positive and significant influence on digital-based learning, accounting for 61.6% of the variance, while the remaining 38.4% is influenced by other factors. The regression equation is ? = 17.978 + 0.764X?. Additionally, self-development has a positive and significant influence on digital-based learning, accounting for 31.5% of the variance, with the remaining 68.5% influenced by other factors. The regression equation is ? = 13.074 + 0.784X?.